Education and Mediated Effects on Economic Development of Indonesia - Jumhur, Jumhur (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Research Originality: This research lies in its comprehensive approach. It utilizes Structural Equation Modeling (SEM) to analyze education levels' direct and indirect impacts on economic growth through various economic indicators.Research Objectives: This study investigates the impact of primary, secondary, and tertiary education levels on Indonesia’s economic growth, specifically examining the mediating effects of Foreign Direct Investment (FDI), credit, exports, and unemployment.Research Methods: The data from the World Development Indicators (WDI) for 2015-2023 offer a long-term perspective on the trends in education and economic performance in Indonesia.Empirical Results: The empirical results indicate that none of the mediators significantly influence the relationship between education levels and Gross Domestic Product (GDP) growth. These challenging conventional theories predict a positive impact of education on economic development. This outcome suggests a potential misalignment between Indonesia’s educational outputs and labor market demand, underscoring the need for policy reforms.Implications: The study implies that to foster meaningful economic growth, Indonesian education policy should enhance curriculum relevance and align educational outcomes with key market needs.JEL Classification: I25, F21, J64